PENGUKURAN KINERJA MENGGUNAKAN RASIO KEUANGAN PADA PT POS INDONESIA (PERSERO) CABANG PAREPARE - Indrayani Indrayani (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2021)
Performance measurement plays an important role in the survival of a company in the business world, because performance measurement becomes a qualification material to determine the efficiency and effectiveness of implementing a predetermined business strategy. Performance measurement can detect the strengths and weaknesses that are still present in the company. The purpose of this study was to determine the financial performance of PT Pos Indonesia (Persero) Cabang Parepare in terms of financial ratios. The method used in measuring financial performance is the method of financial ratios consisting of liquidity ratios, solvency ratios, and profitability ratios. The results of measuring the performance of PT Pos Indonesia (Persero) Cabang Parepare using financial ratios on average obtained by 148% so it can be said that the financial performance at PT Pos Indonesia (Persero) Cabang Parepare